MoU Exchange Ceremony between Beijing Jiaotong University and UMP - Yong, Ying Mei (2019)
Beijing, 10 December 2018 - Delegation of Universiti Malaysia Pahang had an official visit to Beijing Jiaotong University in China. Members of delegation were Professor Dato Sri Daing Nasir Ibrahim (Vice Chancellor of UMP), Professor Dato Dr. Mashitah Binti Mohd Yusoff (Deputy Vice Chancellor-Research & Innovation), Ms. Yong Ying Mei (Director of Confucius Institute, UMP) and Mr. Saharudin Bin Ramli (Senior Executive, Academic & International Affairs, UMP).